Methylmercury exposure causes a persistent inhibition of myogenin expression and C2C12 myoblast differentiation. (15th January 2018) - Prince, Lisa M.; Rand, Matthew D.
Graphical abstract: Abstract: Methylmercury (MeHg) is a ubiquitous environmental toxicant, best known for its selective targeting of the developing nervous system. MeHg exposure has been shown to cause motor deficits such as impaired gait and coordination, muscle weakness, and muscle atrophy, which have been associated with disruption of motor neurons. However, recent studies have suggested that muscle may also be a target of MeHg toxicity, both in the context of developmental myogenic events and of low-level chronic exposures affecting muscle wasting in aging. We therefore investigated the effects of MeHg on myotube formation, using the C2C12 mouse myoblast model. We found that MeHg inhibits both differentiation and fusion, in a concentration-dependent manner. Furthermore, MeHg specifically and persistently inhibits myogenin (MyoG), a transcription factor involved in myocyte differentiation, within the first six hours of exposure. MeHg-induced reduction in MyoG expression is contemporaneous with a reduction of a number of factors involved in mitochondrial biogenesis and mtDNA transcription and translation, which may implicate a role for mitochondria in mediating MeHg-induced change in the differentiation program. Unexpectedly, inhibition of myoblast differentiation with MeHg parallels inhibition of Notch receptor signaling. Our research establishes muscle cell differentiation as a target for MeHg toxicity, which may contribute to the underlying etiology of motor deficits with MeHg toxicity.